Boron Complexes of Glyoxal‐Derived Ugi Adducts as a New Class of Aggregation‐Induced Emission Photoluminescent Materials. Issue 8 (24th March 2017) - Wei, Huiping; Wang, Gaigai; Wang, Yingchun; Li, Binbin; Huang, Jianjun; Kashtanov, Stepan; Van Hecke, Kristof; Pereshivko, Olga P.; Peshkov, Vsevolod A.
Abstract: A series of O, O‐chelated boron complexes was prepared through a four‐component Ugi reaction followed by complexation of the resulting 1, 3‐dicarbonyl compounds with boron trifluoride diethyl etherate. The optical properties of these novel luminophores were investigated by UV/Vis spectroscopy and spectrofluorometry, revealing pronounced aggregation‐induced emission (AIE) features. Abstract : Shine bright like a dAIEmond ! A series of O, O‐chelated boron complexes was prepared through a four‐component Ugi reaction followed by complexation of the resulting 1, 3‐dicarbonyl compounds with boron trifluoride diethyl etherate. The optical properties of these luminophores were investigated, revealing pronounced aggregation‐induced emission (AIE) features.